2006
DOI: 10.1103/physreve.73.036306
|View full text |Cite
|
Sign up to set email alerts
|

Bubble behavior in a Taylor vortex

Abstract: -We present an experimental study on the behavior of bubbles captured in a Taylor vortex. The gap between a rotating inner cylinder and a stationary outer cylinder is filled with a Newtonian mineral oil. Beyond a critical rotation speed (ω c ), Taylor vortices appear in this system. Small air bubbles are introduced into the gap through a needle connected to a syringe pump. These are then captured in the cores of the vortices (core bubble) and in the outflow regions along the inner cylinder (wall bubble). The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 9 publications
3
8
0
Order By: Relevance
“…In the grand-canonical ensemble, the fit yields C 2,0 = 0.039 446 (4) and c g = 0.105 5 (7); the former is consistent with the existing result C 2,0 = 0.039 44(4) [28], the latter agrees well with the exactly known value c = 0.105 436 634 [19]. In the canonical ensemble, the result is C 2,0 = 0.039 446 (6) and c c = −0.33 (5).…”
Section: Numerical Resultssupporting
confidence: 89%
“…In the grand-canonical ensemble, the fit yields C 2,0 = 0.039 446 (4) and c g = 0.105 5 (7); the former is consistent with the existing result C 2,0 = 0.039 44(4) [28], the latter agrees well with the exactly known value c = 0.105 436 634 [19]. In the canonical ensemble, the result is C 2,0 = 0.039 446 (6) and c c = −0.33 (5).…”
Section: Numerical Resultssupporting
confidence: 89%
“…The almost linear relationship between the maximum radial velocity and Re agrees with the theoretical analysis provided by Czarny et al24 Moreover, the relationship can explain the profile of maximum bubble size that can be captured in a Taylor vortex at various Re 19. However, this is different from Davey's nonlinear correlation between axial (or radial) velocity and reduced Re in an infinitely long liquid column 25.…”
Section: Resultssupporting
confidence: 85%
“…A schematic diagram of the experimental apparatus is shown in Figure 1, which is similar to the system used by Deng et al19 A Newtonian mineral oil (with a density ρ of 0.86 g/cm 3 and a viscosity μ of 0.0297 Pa s) was used as the working fluid between a rotating inner cylinder ( R i = 18.4 mm, H = 60 mm) and a stationary outer cylinder ( R o = 30 mm, L = 200 mm). This gives a gap width d of 11.6 mm, a radius ratio η = R i / R o of 0.613, and an aspect ratio Γ of 5.17.…”
Section: Methodsmentioning
confidence: 99%
“…They concluded that bubble accumulation on the downward side of vortices was primarily due to the lift force, in what is known as the preferential sweeping mechanism. Deng, Wang & Smith (2006) experimentally investigated the behaviour of bubbles in a Taylor vortex wherein the drag and buoyancy forces are in balance, in line with later observation in this work. Lohse & Prosperetti (2003) studied the equilibrium position of a bubble in a horizontally rotating cylinder and suggested the need for future studies investigating different lift models.…”
Section: Vortex-bubble Interactionsupporting
confidence: 60%